Exploring new terrain - tackling a tri-media approach to the 1999 election: an analysis of online coverage of elections by media organisations in their respective countries and recommendations for multi-platform publishing within the South African Broadcasting Corporation to cover the national election - Naidoo, Kameshnee (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 1999)
This study attempts to analyse the way foreign media organisations have used the Internet to inform, educate and mobilise citizens for participation in their national election. These foreign experiences provide a framework with which to analyse the implications for the SABC as a public broadcaster of the next elections in South Africa. The research was informed by theories of media and democracy. One of the most powerful features of the new technology is its technical ability to facilitate an interactive flow of information. This research examines the concept of cyberdemocracy and the implications for the SABC, especially as it is planning on launching an online election strategy. The democratic roles of journalism and the implications for the SABC are also discussed. As a public service broadcaster, the SABC is bound to educate, inform, and mobilise voters for participation, build community and national identity and scrutinise the poll in the interests of transparency, accountability and fair play. International journalists are advocating a new type of journalism, called public or civic journalism, which combines these roles. This research draws primarily on qualitative research methods, using a case study methodology. It draws upon direct observation and interview methodology in the fieldwork. However, it also uses some quantitative methods in the analysis of the websites and the SABC research.Finally, the research analyses the situation at the SABC and provides recommendations for the election website within this context.
Keywords: South African Broadcasting Corporation; Elections; Journalism -- Political aspects -- South Africa; Mass media -- Political aspects -- South Africa; Internet; Electronic news gathering; Television broadcasting of news -- Political aspects